Platformed Communities and the Emergence of Synthetic Creator Cultures - Wiehn, Tanja ; 0000-0002-9657-5292 (Platforms & Society, 2026)
As posited in this themed issue, the notion of platformed communities accounts for a multitude of relations between users, content creators and platforms. This article analyses how synthetic influencers negotiate existing practices of community building in creator cultures. It frontloads how boundaries of communal and commodified online environments are further blurred in platformed cultural production when technological elements extend the ways in which creators practice relational labour, authenticity and accessibility with their audiences. For this, the article opens existing scopes of what synthetic influencers constitute. It considers synthetic creators managed by agencies, as well as creators that extend their platform presence via deep fake livestreams and generative AI technologies. The article draws on key theoretical perspectives from platform studies and creator studies. Methodologically, it applies a case study approach that allows the incorporation of a diverse set of materials.
Keywords: Synthetic influencers; content creators; platforms; communities; platformed communities; cultural production